2020
DOI: 10.1002/cncr.33049
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcome of adjuvant chemotherapy in deficient mismatch repair stage III colon cancer

Abstract: Background The prognostic impact of DNA mismatch repair (MMR) status remains controversial in patients with stage III colon cancer who are treated with adjuvant chemotherapy (AC). The aim of this study was to evaluate the survival outcome of AC in deficient mismatch repair (dMMR)/microsatellite instable (MSI) stage III CC. Methods Patients with pathological stage III CC between 2010 and 2013 were identified from the National Cancer Database using International Classification of Diseases for Oncology (3rd Editi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The present study showed that the survival difference between cecum cancers and sigmoid colon cancers is the largest among the six colon sites, which is akin to the results of Shaib et al [ 21 ]. By analyzing the data of patients with non-metastatic, invasive right-sided adenocarcinoma of the colon from 1988 to 2014 who underwent partial colectomy in SEER, Nasseri at al found that cecum cancers were prone to poorer disease-specific survival (median 86.0, 93.0, and 89.0 months, respectively, p < 0.001) and OS (median not reached, p < 0.001) compared with cancers in other sites of the right colon [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study showed that the survival difference between cecum cancers and sigmoid colon cancers is the largest among the six colon sites, which is akin to the results of Shaib et al [ 21 ]. By analyzing the data of patients with non-metastatic, invasive right-sided adenocarcinoma of the colon from 1988 to 2014 who underwent partial colectomy in SEER, Nasseri at al found that cecum cancers were prone to poorer disease-specific survival (median 86.0, 93.0, and 89.0 months, respectively, p < 0.001) and OS (median not reached, p < 0.001) compared with cancers in other sites of the right colon [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the conflicting results may be partly due to the inconsistency of location grouping criteria, and the dichotomy model (right-sided vs. left-sided colon) may be inappropriate for the study of colon cancer [ 16 , 17 , 18 , 19 ]. Moreover, the prognostic differences between specific subsites (cecum, ascending colon, hepatic flexure, transverse colon, splenic flexure, descending colon, and sigmoid colon) have also been reported in a few studies [ 19 , 20 , 21 ]. In order to further explore the effects of tumor locations on prognosis, it is essential to find two parts with the greatest survival differences by comparing different primary tumor locations.…”
Section: Introductionmentioning
confidence: 95%
“…Although MSI/dMMR is a positive prognostic factor for stage II colon cancer after curative resection, the prognostic impact of MSI/dMMR status remains controversial in patients with stage III colon cancer who have received postoperative adjuvant chemotherapy [ 30 – 32 ]. In some conditions, for example, proximal colon cancer or adjuvant chemotherapy with multiple regimens, patients with stage III colon cancer and MSI/dMMR tumors who received oxaliplatin-based adjuvant chemotherapy had better survival outcomes [ 33 , 34 ]. Moreover, the presence of BRAF status, which occurs in approximately 10% of colorectal cancer, has been considered a predictive marker in the survival of patients with metastatic colorectal cancer because the mutation status correlates with lower therapeutic response to chemotherapy with or without target agents [ 35 ].…”
Section: Discussionmentioning
confidence: 99%